Adsorption of charged macromolecules upon multicomponent responsive surfaces. Issue 30 (23rd July 2018) - Nunes, Sandra C.C.; Cova, Tânia F. G. G.; Dias, Rita S.; Pais, Alberto A. C. C.
Abstract : A predictive model for polyelectrolyte adsorption upon responsive surfaces is presented, decoupling the effect of surface charges and crowders. Abstract : Adsorption of polyions onto charged surfaces has long been recognized as a crucial phenomenon in biological and technological applications. An intuitive model relating polyelectrolyte adsorption with the imposed features of polarizable surfaces of different compositions and charges is proposed based on Monte Carlo simulations using a coarse-grained approach. The excellent performance of the equation allows simultaneously describing a wide range of adsorption regimes and accounting for specific non-monotonic trends. For a constant surface charge density, the surface composition governs adsorption, promoting variations exceeding 100%. Adsorption increases with the number of attractive charges in the surface until reaching a maximum, decreasing thereafter due to the presence of polyanion-like charged particles. The presence of crowders hampers adsorption. These results can be used to efficiently predict and modulate the interaction between charged macromolecules and different substrates with direct implications in de novo designs of vehicles and biomedical devices.